Exploring the S-shaped relationship between triglyceride-glucose index and serum uric acid levels in individuals with osteoporotic fracture - Zhou, Xiao-jie; Xu, Min-zhe; Gong, Ya-qin; Jin, Jian; Lu, Ke; Li, Chong (Frontiers in Endocrinology, 2025)
BackgroundThe triglyceride-glucose index (TyG) has been linked to metabolic disorders, yet its association with serum uric acid (SUA) in elderly osteoporosis patients remains unclear. This study aimed to determine whether TyG independently correlates with SUA levels in osteoporotic fracture (OPF) patients aged >50 years.MethodsThis was a retrospective cross-sectional analysis of data from 2,152 OPF patients from the Affiliated Kunshan Hospital of Jiangsu University database hospitalized between January 2017 and July 2022. Baseline TyG was the exposure variable, whereas SUA levels were the study outcome. When analyzing this relationship, adjustments were made for age, gender, BMI, and various baseline clinical and laboratory parameters, followed by the fitting of separate univariate and multivariate linear regression models. Non-linear association analyses were also conducted with the generalized additive model (GAM). This relationship was further characterized through smooth curve fitting, univariate analysis, and threshold effect analyses.ResultsAfter adjusting for confounders, an S-shaped relationship between TyG and SUA levels was identified and fitted to a two-piecewise linear regression model with inflection points at 6.34 and 8.09 (P-value for LRT < 0.01). Significant positive correlation was observed within the range 6.34–8.09 (β = 27.73, 95% CI: 18.72–36.75, P < 0.01), whereas no significant association was found below or above this range.ConclusionsThis study demonstrates a non-linear S-shaped relationship between TyG and SUA levels in OPF patients, with a significant correlation observed only within a specific TyG range. These findings provide novel insights into the metabolic implications of TyG in elderly individuals with osteoporosis.